A miniature Stirling cryocooler operating above 100 Hz down to liquid nitrogen temperature. (5th March 2021) - Bo, Wang; Yijun, Chao; Haoren, Wang; Qinyu, Zhao; Dongli, Liu; Zhihua, Gan
Highlights: A Stirling crycooler operating above 100 Hz was designed based on AcME theory. The cryocooler reached a no-load temperature of 77.1 K at 105 Hz and 2.50 MPa. A net cooling power of 0.28 W was obtained at 90.0 K. Performance of the cryocooler will be improved with a more efficient compressor. Abstract: Working temperature of infrared detectors increases to higher than 100 K with the breakthrough of infrared materials, and the HOT (High Operation Temperature) cryocoolers with features of low weight and volume for infrared detectors cooling are now attracting more attentions. Increasing the operating frequency of the Stirling cryocooler to ultra-high level (>100 Hz) can significantly reduce the volume and weight of it, but the complicated acoustic and mechanical coupling inside the Stirling cryocooler limits the efficiency of Stirling cryocoolers operating above 100 Hz. In this paper, a pneumatically driven split-Stirling cryocooler operating above 100 Hz is designed and fabricated based on the Acoustic-Mechanical-Electrical (AcME) coupling method, and the cryocooler achieves a no-load temperature of about 77 K and the net refrigeration power at 90.0 K is 0.28 W. The operating frequency is 105 Hz and the charging pressure is 2.50 MPa. To the knowledge of the authors, the cryocooler is the first pneumatically driven split-Stirling cryocooler operating above 100 Hz working at liquid nitrogen temperature. This study confirms the feasibility of AcME coupling method, and the optimized design of ultra-high working frequency Stirling cryocooler based on this method.